Fracture life estimation of Al-1050 thin beams using empirical data and a numerical approach - Khan, Muhammad Ali; Khan, Kamran Ahmed; Nisar, Salman; Starr, Andrew (British Institute of Non-destructive Testing, 2018)
A technique based on empirical data and finite element (FE) analysis to predict the fracture life of Al-1050 beams with the help of its fundamental mode is presented in this study. Experiments were performed on a non-prismatic beam vibrating with a constant value of the amplitude at the fixed end until the complete fracture of the specimen was achieved. The beam was vibrating at its fundamental mode to achieve fracture in less time. A power law model was used to acquire the possible trends between the values of natural frequencies and the number of cycles recorded during these experiments. These trends were further compared with a numerically modelled specimen but with artificial cracks. FE modal analysis was used for this comparison. An error of less than 1% was observed in the estimated number of total cycles obtained through the power law model before fracture, compared to those obtained using the numerical approach. Using this approach, the fracture life was also predicted for specimens of different lengths.
Keywords: Artificial cracks; Modal analysis; Power law; Finite element analysis; Fracture